1980
DOI: 10.3758/bf03204316
|View full text |Cite
|
Sign up to set email alerts
|

A reevaluation of angle-contingent color aftereffects

Abstract: It has been argued that adaptation to a series of angles with vertices pointing up and illuminated in one color, and to angles with vertices pointing down and illuminated in the opponent color, results in color aftereffects that are contingent on angle direction. In the present paper, using a number of test figures, we demonstrate that adaptation to these ascending/descending angles results in color aftereffects that can be accounted for in terms of spatially localized, orientation-color pairings. In the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…concluded that the color aftereffects they obtained were orientation contingent rather than angle contingent, and they argued that these orientation路contingent color aftereffects were retinally specific. Additional data in support of the Hayman and Allan (1980) conclusion are reported. These data point to the important role of eye fixations and eye movements on contingent color aftereffects.…”
supporting
confidence: 56%
“…concluded that the color aftereffects they obtained were orientation contingent rather than angle contingent, and they argued that these orientation路contingent color aftereffects were retinally specific. Additional data in support of the Hayman and Allan (1980) conclusion are reported. These data point to the important role of eye fixations and eye movements on contingent color aftereffects.…”
supporting
confidence: 56%
“…In fact, there has even been debate about aftereffects contingent on features such as curvature and angle. Although some investigators claim to have found color aftereffects contingent on curvature (Cavill & Robinson, 1976;Riggs, 1973Riggs, , 1974White & Riggs, 1974) or on angle (White & Riggs, 1974), others have argued that these aftereffects are really contingent on orientation (Allan & Hayman, 1982;Crassini & Over, 1975;Hayman & Allan, 1980;MacKay & MacKay, 1974;Sigel & Nachmias, 1975;Stromeyer, 1974).…”
mentioning
confidence: 99%
“…Others, however, have not been able to obtain effects under similar induction conditions in which the pattern moved relative to the retina (Mackay & MacKay, 1974;Sigel & Nachmias, 1975;Stromeyer, 1974). Furthermore, Hayman and Allan (1980) found that there were changes in the hue reported as a result of shifts in the locus of fixation on test figures and that these changes were those that were expected on the basis ofspatially localized aftereffects. On balance, it appears that chevron-like patterns produce highly localized orientation-contingent aftereffects.…”
Section: Discussionmentioning
confidence: 81%
“…White and Riggs (1974;see also Riggs, 1973) have proposed that such patterns contain angles and adapt mechanisms that are sensitive to the direction of departure from a straight line. Many other results suggest, however, that induction with angled or curved line patterns can be accounted for in terms of adaptation of mechanisms sensitive to line orientation and retinal position (e.g., Crassini & Over, 1975;Hayman & Allan, 1980;Sigel & Nachmias, 1975). White and Riggs argued that the color aftereffects cannot be due to local color and orientation contingencies, because they obtained color aftereffects when subjects slowly scanned the patterns.…”
Section: Discussionmentioning
confidence: 99%